Tolak Bala: A Relation Between Islam and Tradition - Syarifah Sajila Apjan (Universitas Islam Negeri (UIN) Salatiga, 2019)
Islam and tradition are two different sides, they are debated when they are related. The topic has some similarities to the reality of some of today's society in addressing the differences of disputes and debates. This article is a research that aims to provide views and knowledge to public by researching the relations of Islam and traditions in the coastal areas of Dabong community, Kubu Subdistrict, District of Kubu Raya, West Kalimantan. Terminology of Islam and traditions which is not interconnected, can realize relationships and local wisdom. The research method used is qualitative research with the technique of data collection through interview. The subject of this research is the coastal community of Dabong, Kubu District, Regency of Kubu Raya, West Kalimantan. The results show that (1) The public understand that not all traditions are wrong even have Islamic values, and (2) Open the public's view that the difference is not an arena of debate, but a material to strengthen togetherness. The relationship between Islam and tradition can also open the public's view of peace, harmony, prosperity, so that can be concluded as a connecter of the nation.